Air exposure induced recombination in PTB7:PC71BM solar cells. Issue 41 (12th October 2017) - Thomson, Stuart A. J.; Hogg, Stephen C.; Samuel, Ifor D. W.; Keeble, David J.
Abstract : Magnetic resonance identifies oxidised PC71 BM recombination centres in PTB7:PC71 BM solar cells processed when using DIO and exposed to air. Abstract : Understanding degradation pathways in organic photovoltaic cells (OPV) is essential to achieve long term device stability and allow commercialisation. Upon exposure to an ambient atmosphere the power conversion efficiency (PCE) of PTB7:PC71 BM solar cells, cast using the solvent additive DIO, is markedly reduced. Using electrically detected magnetic resonance (EDMR) spectroscopy, trap sites, which are formed when the blend is exposed to air and DIO, are identified. Spin-Rabi oscillations reveal that the resonance arises from a weakly coupled pair of spin 1/2 species, while selective injection of charge carriers into the cell demonstrates that the spin-pair corresponds to recombination of electrons and holes. The recombination is assigned to holes on the PTB7 recombining with electrons localised to oxygen induced PC71 BM trap sites.